Unusual presentation of cutaneous leishmaniasis - P S Sindhu; V Ramesh (Wolters Kluwer Medknow Publications, 2012)
Two patients with mini-volcano type of skin lesions which showed histopathologic features of cutaneous leishmaniasis (CL) have been described. It was localised and linear in one case while widespread in the other. Both responded to sodium stibogluconate. The importance of recognising new emerging foci of CL is emphasised.